Health education actions in the primary attention: revealing methods, techiniques and theoretical basis - Alexsandra Rodrigues Feijão; Marli Teresinha Gimeniz Galvão (Rev Rene)
The aim of this study was to investigate the main techniques and methods of education as far as health is concerned and also their relationship with the education theoretical basis used by health professionals in the elaboration and implementation of educational actions in health, within the scope of the primary attention It was Developed a systematic review in five Brazilian newspapers, within the period of 1990 to 2004. The descriptors used were: Education; Education in Health; Primary Attention in Health and Health Promotion. The 58 articles selected were categorized according to similarities of subjects and approaches. As a result of the analysis we were led to conclude that education in health can be considered one of the main actions of health promotion, considering that it is of great importance not only in the prevention and rehabilitation of illnesses, besides raising conscious citizenship, social and personal responsibility related to health, but also in the formation of multipliers and care takers.